Identification of photoperiod-induced specific miRNAs in the adrenal glands of Sunite sheep (Ovis aries) - Du, Xiaolong; He, Xiaoyun; Liu, Qingqing; Liu, Qiuyue; Di, Ran; Chu, Mingxing (Frontiers in Veterinary Science, 2022)
In seasonal estrus, melatonin-regulated biorhythm is well known to play a key role, but this is only a small part of the complex reproductive process. Some studies indicate that the adrenal gland plays an important role in reproduction in mammals, but the molecular mechanism is not clear. In this study, an artificial controlled light photoperiod model, combined with RNA-seq technology and bioinformatics analysis, was used to analyze the messenger RNA (mRNA) and microRNA (miRNA) of sheep adrenal glands under different photoperiod treatments. After identification, the key candidate genes GRHL2, CENPF, FGF16 and SLC25A30 that photoperiod affects reproduction were confirmed. The miRNAs (oar-miR-544-3p, oar-miR-411b-5p, oar-miR-376e-3p, oar-miR-376d, oar-miR-376b-3p, oar-miR-376a-3p) were specifically expressed in the adrenal gland but not in the hypothalamus of Small Tail Han sheep. The candidate mRNA-miRNA pairs (e.g., SLC25A30 coagulated by novel miRNA554, novel miRNA555 and novel miRNA559) may affect seasonal oestrus. This study comprehensively analyzed the mRNAs and miRNAs of sheep adrenal glands, which provided valuable resources for elucidating the fecundity of sheep.